A Randomized Comparison of Two Doses of Tranexamic Acid in High-Risk Open-Heart Surgery - Shrestha, Battu Kumar; Khadka, Rima; Bhusal, Surendra; Baidya, Rabin; Bhandari, Sandip; KC, Suraj (Nepalese Heart Journal, 2023)
Background and aims: Tranexamic acid is commonly used in cardiac surgery to minimize perioperative bleeding. There are wide variations in dose of this drug. This study aims to find out the minimal effective dose of tranexamic acid. Methods: Patients were randomized into low dose group receiving 10 mg/kg and high dose group receiving 30 mg/kg bolus of tranexamic acid each followed by an infusion of 1mg/kg/hr until the end of surgery. Primary objective was to compare blood loss during the first postoperative day. Secondary objectives were to compare total blood products transfused during 24 hours post-operative period, to compare the incidence of re-explorations and to compare the adverse drug reactions between the groups. Results: There were sixty patients in each group. There was a signifcant difference in blood loss (435.17± 299.91 ml vs 528.64 ±254.04 ml) between the low dose group and dose group (p=0.010). Transfusion of packed red blood cell, re-exploration and adverse drug reactions were higher in high dose group however these were not statistically signifcant. Conclusion: Higher dose of tranexamic acid is not effective in reducing blood loss in open heart surgery in first postoperative day.